Erosion and Sedimentation Analysis of the Sario Sub-Watershed, Manado City, North Sulawesi: A USLE-GIS Approach - Pangemanan, Dimas; Walangitan, Henki; Kalangi, Josephus; Saroinsong, Fabiola (Asia Pacific Journal of Interdisciplinary Studies, 2026)
The Sario Sub-Watershed is a densely populated urban catchment in Manado City, North Sulawesi, that drains directly into Manado Bay and is prone to recurring floods and riverbed siltation. This study analyzed the rate of soil erosion and the amount of sediment reaching the Sario River in the downstream part of the sub-watershed, an area not yet specifically assessed by earlier studies covering the whole Sario watershed. Erosion was estimated using the Universal Soil Loss Equation (USLE) integrated with a Geographic Information System (GIS), combining rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), land cover (C), and conservation practice (P) factors derived from ten years (2015-2024) of rainfall data, soil and land-cover maps, and a Digital Elevation Model. The resulting sediment yield delivered to the river was then estimated using the Sediment Delivery Ratio (SDR) of Auerswald (1992) and the Boyce method. Results show a total annual erosion of 715,436.74 tons across 1,207.10 ha, or an area-weighted average of 592.69 tons/ha/year, placing the sub-watershed in Erosion Hazard Class V (very severe) under Indonesian Ministry of Forestry Regulation No. 32/2009. Class V areas cover 596.96 ha (49.45%), concentrated on steep, densely settled terrain dominated by Eutric Cambisol soil. The estimated SDR of 0.291 yields a sediment load of 208,191.90 tons/year reaching the Sario River. These findings indicate that erosion and sedimentation in the sub-watershed are driven mainly by steep topography combined with low-conservation-value settlement land, underlining the need for forestry-based watershed interventions such as land rehabilitation, urban green open space development, riparian buffer strips, and agroforestry to reduce erosion, sedimentation, and recurrent flooding.